The role of chemokine C-C motif ligand 2 genotype and cerebrospinal fluid chemokine C-C motif ligand 2 in neurocognition among HIV-infected patients - Thames, April D. (AIDS, 2015)
OBJECTIVES: We examined interrelationships between chemokine C-C motif ligand 2 (CCL2) genotype and expression of inflammatory markers in the cerebrospinal fluid (CSF), plasma viral load, CD4(+) cell count and neurocognitive functioning among HIV-infected adults. We hypothesized that HIV-positive carriers of the ‘risk’ CCL2 −2578G allele, caused by a single nucleotide polymorphism (SNP) at rs1024611, would have a higher concentration of CCL2 in CSF, and that CSF CCL2 would be associated with both higher concentrations of other proinflammatory markers in CSF and worse neurocognitive functioning. DESIGN: A cross-sectional study of 145 HIV-infected individuals enrolled in the National NeuroAIDS Tissue Consortium cohort for whom genotyping, CSF and neurocognitive data were available. METHODS: Genomic DNA was extracted from peripheral blood mononuclear cells and/or frozen tissue specimens. CSF levels of CCL2, interleukin (IL)-2, IL-6, tumour necrosis factor-alpha (TNF-α), interferon-gamma (IFN-γ), soluble tumor necrosis factor receptor 2, sIL-6Rα, sIL-2, sCD14 and B-cell activating factor were quantified. Neurocognitive functioning was measured using a comprehensive battery of neuropsychological tests. RESULTS: Carriers of the CCL2 −2578G allele had a significantly higher concentration of CCL2 in CSF. CSF CCL2 level was positively and significantly associated with other CSF neuroinflammatory markers and worse cognitive functioning. There was a significant association between genotype and plasma viral load, such that carriers of the CCL2 −2578G allele with high viral load expressed greater levels of CCL2 and had higher neurocognitive deficit scores than other genotype/viral load groups. CONCLUSION: Individuals with the CCL2 −2578G allele had higher levels of CCL2 in CSF, which was associated with increased pro-inflammatory markers in CSF and worse neurocognitive functioning. The results highlight the potential role of intermediate phenotypes in studies of genotype and cognition. VIDEO ABSTRACT: http://links.lww.com/QAD/A699